The role of capsid in the flaviviral life cycle and perspectives for vaccine development - He, Yu (Vaccine, 2020)
The arthropod-borne flaviviruses cause a series of diseases in humans and pose a significant threat to global public health. In this review, we aimed to summarize the structure of the capsid protein (CP), its relevant multiple functions in the viral life cycle and innovative vaccines targeting CP. The flaviviral CP is the smallest structural protein and forms a homodimer by antiparallel α-helixes. Its primary function is to package the genomic RNA; however, both steps of assembly and dissociation of nucleocapsid complexes (NCs) have been obscure until now; in fact, flaviviral budding is NC-free, demonstrated by the subviral particles that generally exist in flavivirus infection. In infected cells, CPs associate with lipid droplets, which possibly store CPs prior to packaging. However, the function of nuclear localization of CPs remains unknown. Moreover, introducing deletions into CPs can be used to rationally design safe and effective live-attenuated vaccines or noninfectious replicon vaccines and single-round infectious particles, the latter two representing promising approaches for innovative flaviviral vaccine development.